2007
DOI: 10.2174/187425640701011004
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Characteristics, Antimicrobial and Mutagenic Activity in Organically and Conventionally Produced Malus domestica, Annurca

Abstract: Total polyphenols content and a partial phenolics composition from pulp and peel of organically and conventionally produced Malus domestica, Annurca were investigated. Furthermore, the antimicrobial effect of these compounds against useful and pathogen microorganism was examined. Finally, their mutagenic activities were evaluated. Organically grown apples showed a greater content of polyphenols, both into the pulp and the peel. The distribution of polyphenols was different between the two types of fruit, the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…The maximum inhibition zone against P. aeruginosa was observed in case of antibiotic followed by peel extract with mean inhibition zone of 19.00 mm and 13.50mm, respectively and the minimum inhibition was observed in case of pomace extract with mean inhibition zone of 9.05 mm. The results were closely related to the findings of Fratianni et al [31]. Who observed 6 mm to 13mm inhibitory zone of apple extracts against E. coli.…”
Section: Evaluation Of Antimicrobial Activity Of Various Extracts Of supporting
confidence: 90%
“…The maximum inhibition zone against P. aeruginosa was observed in case of antibiotic followed by peel extract with mean inhibition zone of 19.00 mm and 13.50mm, respectively and the minimum inhibition was observed in case of pomace extract with mean inhibition zone of 9.05 mm. The results were closely related to the findings of Fratianni et al [31]. Who observed 6 mm to 13mm inhibitory zone of apple extracts against E. coli.…”
Section: Evaluation Of Antimicrobial Activity Of Various Extracts Of supporting
confidence: 90%
“…The increasing number of research studies have found that apples can possess some antimicrobial activity. Conventionally produced apples inhibited Bacillus cereus , while the organic peel demonstrated antimicrobial activity against Escherichia coli 0157:07 [ 47 ]. It was also reported that the presence of phloretin and its glycosylated derivatives in apples are able to inhibit growth of Gram-positive bacteria, and are active against some strains of the Gram-negative bacteria [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…In another study by Florida Fratianni et al .,[ 10 ] antimicrobial effect of two varieties of apples: organically produced and conventionally produced apples were tested against useful lactobacillus species and pathogenic microorganisms, i.e., Bacillus cereus , which is responsible for several cases of foodborne illness and the enterohemorrhagic E. coli , that causes serious cases of food poisoning. None of the apple extracts assayed gave positive results against the 6 strains of lactic acid bacteria.…”
Section: Discussionmentioning
confidence: 99%